2019
DOI: 10.7759/cureus.5669
|View full text |Cite
|
Sign up to set email alerts
|

“D” is for Dilemma

Abstract: Immunoglobulin D (IgD) monoclonal gammopathy is a rare subtype of multiple myeloma (MM) associated with a worse prognosis compared with other variants of MM. A 61-year-old man with no known past medical history presented with complaints of abdominal pain, nausea, and vomiting for three weeks. Physical examination revealed mild epigastric tenderness. Laboratory data demonstrated a significantly elevated creatinine with minimal proteinuria and small abnormality in the gamma fraction. Ultrasound of the kidneys de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Research results of Hoekman et al [41] showed that in twelve types of biodiesel, the range of kinematic viscosity was from 4 to 5 mm 2 /s. According to Table 7, it is clear that the flash point, pour point, acid value, and oxidative stability are consistent with reports from other researchers [21,22,42]. It is important to note here that the properties of the produced biodiesel are in the range of the standard-defined properties (ASTM D6751 and EN 14112).…”
Section: Optimization Of the Production Process Using Desirability Fusupporting
confidence: 87%
See 1 more Smart Citation
“…Research results of Hoekman et al [41] showed that in twelve types of biodiesel, the range of kinematic viscosity was from 4 to 5 mm 2 /s. According to Table 7, it is clear that the flash point, pour point, acid value, and oxidative stability are consistent with reports from other researchers [21,22,42]. It is important to note here that the properties of the produced biodiesel are in the range of the standard-defined properties (ASTM D6751 and EN 14112).…”
Section: Optimization Of the Production Process Using Desirability Fusupporting
confidence: 87%
“…The results showed that using ultrasound irradiation reduces the reaction time, while the conversion percent and the quality of the biodiesel were the same as those of the conventional method. Kumar et al [21] investigated the effect of using ultrasound irradiation on decreasing the reaction time of biodiesel production from coconut oil. The results of their study indicated that using ultrasound irradiation reduces the reaction time by 15-40 min.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulin D multiple myeloma (IgD MM) is a rare isotype of multiple myeloma (MM), comprising less than 2% of all cases. It is often associated with an aggressive clinical course and a worse prognosis than other MM variants (1,2).…”
Section: Introductionmentioning
confidence: 99%